Preponderance of Evidence - Dominique Demougin; Claude Fluet (Center for Economic Studies and ifo Institute (CESifo), 2002)
This paper analyzes the incentive properties of the standard and burden of proof for a finding of negligence, when evidence is imperfect and rests with the parties. We show that the preponderance of evidence' standard provides maximal incentives to exert care. This holds even though litigants may have unequal access to evidence and distort information. The optimal assignment of the burden of proof follows from the principle underlying the standard of proof. Our main results are derived in a mechanism design framework, but we also consider implementation as a sequential equilibrium with the court as a player in the game.
Keywords: 330; negligence; standard of proof; tort rules; burden of proof; deterrence